The Impact of Social Behavior and Peers’ Attitudes Toward Students With Special Educational Needs on Self-Reported Peer Interactions - Schwab, Susanne; Lehofer, Mike; Tanzer, Norbert (Frontiers in Education, 2021)
According to the literature, social participation (e.g., peer interactions) of students diagnosed with special educational needs (SEN) has to be focused upon as they are at a higher risk of being socially excluded compared to students without SEN. Research has pointed out that social participation of students with SEN is influenced by their own social behavior as well as the attitudes of peers with no SEN toward them. The present study assessed the impact of the social behavior of students diagnosed with SEN (n = 88; 48 boys and 40 girls) as well as that of the attitudes of their peers without SEN (n = 227; 139 boys and 153 girls) toward them on the social participation. Results indicated that students without SEN were less likely to interact with their classmates with SEN. Peer interactions of students with SEN were not significantly influenced by their own social behavior.